Learning and Study Strategies : Issues in Assessment, Instruction, and Evaluation. - Edwards, Allen J. (Elsevier Science, 2014)
This volume reflects current research on the cognitive strategies of autonomous learning. Topics such as metacognition, attribution theory, self-efficacy, direct instruction, attention, and problem solving are discussed by leading researchers in learning and study strategies. The contributors to this volume acknowledge and address the concerns of educators at the primary, secondary, and postsecondary school levels. The blend of theory and practice is an important feature of this volume.